(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: It is not known in which way neurohumoral properties of the hypothalamus undergo changes due to traumatic optic nerve neuropathy (TON). Purpose: To investigate the value of neurohumoral dysfunction in the pathogenesis of TON. Materials and Methods: Trauma was induced in the right orbital optic nerve in adult rabbits (n = 30, the experimental group). Controls were 30 intact rabbits. Semi-fine and ultra-fine sections were cut, and electron microscopy and morphometry of the right intracranial optic nerve and suprachiasmic hypothalamus nucleus was performed 30 days after traumatic event. Results: Traumatic injury to the orbital optic nerve in rabbits caused reactive edema and destructive changes in the intracranial optic nerve and suprachiasmic hypothalamus nucleus. Decreased volumetric density of neurosecretory granules and increased numbers of pyknomorphic cells at the final stages of their life cycle result in decreased steroid production. This, in turn, promotes inflammatory reactive optic nerve lesions. Conclusion: Neurohumoral dysfunction is an important mechanism of the pathogenesis of traumatic optic neuropathy, and, if corrected, will improve treatment outcomes.